ALK Immunohistochemistry in NSCLC: Discordant Staining Can Impact Patient Treatment Regimen. Issue 12 (December 2016) - Ibrahim, Merdol; Parry, Suzanne; Wilkinson, Dawn; Bilbe, Neil; Allen, David; Forrest, Steven; Maxwell, Perry; O'Grady, Anthony; Starczynski, Jane; Tanier, Philippe; Gosney, John; Kerr, Keith; et al.
ABSTRACT : Introduction: : Diagnostic immunohistochemistry (IHC) is increasingly accepted as a screening method for anaplastic lymphoma receptor tyrosine kinase gene ( ALK ) rearrangements in NSCLC. We have sought to establish an ongoing robust external quality assessment process to gauge quality of anaplastic lymphoma kinase (ALK) IHC, which can have an impact on interpretation of patient samples. Methods: : Unstained tissue and cell line samples were distributed on a quarterly basis to participating laboratories from 30 countries. Participants stained the slide using their routine diagnostic ALK IHC method and returned the slide along with their in‐house control and methodology details. Slides were assessed by a team of pathologists and scientists. Results: : Overall, there was a mean pass rate of 83% (range 71%–98%), with 38 variations in staining protocol. Methods included the following: the Roche D5F3 assay (65% of users, pass rate 93%); Novocastra 5A4 (15% of users, pass rate 65%); Cell Signaling Technology D5F3 (7% of users, pass rate 91%), and Dako ALK1 (5% of users, pass rate 50%). Choice of methodology directly affected final interpretation of distributed ALK‐positive and ALK‐negative NSCLC cases, which were correctly identified by 89% and 88% of participants, respectively. Antibody detection method was a contributing factor in false‐negative staining results. The choice of laboratory controls was found to be unsuitable, and as such, in‐house control recommendations are also provided. Conclusions: : ALK IHC is a robust screening technique, but there is concern that some diagnostic laboratories are using inadequate staining methods, which has a direct impact on final interpretation. External assessment helps provide laboratories with continued confidence in their ALK IHC testing.